Аналіз ринку харчових продуктів з харчовими барвниками - Івчук, Надія Павлівна; Башта (Шеремет), Алла Олексіївна (My University, 2015)
Метою даного дослідження було встановити, який відсоток харчових продуктів має у своєму складі харчові барвники, до якої групи вони відносяться та у виробництві яких видів харчових продуктів використовуються. Виявлено, що натуральні харчові барвники використовуються у виробництві 39 % харчових продуктів. У 12 % досліджуваних харчових продуктів виявлено синтетичні харчові барвники. Вони зустрічаються у кондитерських виробах (64 %) та безалкогольних напоях (26 %). Саме ці продукти найчастіше споживають діти, тому й існує реальна загроза їхньому здоров ’ю та майбутньому нації. The purpose of this study was to determine what percentage of food products has in its structure food dyes, to which group they belong and in manufacture of what types of food they are used. Monitoring of the chemical composition of food has shown that food dyes present in 51% of the investigated product. Found that natural food dyes used in production of 39% of food products. In 12% of the studied food products found synthetic food dyes. Most of them are found in confectionery products (64%) and soft drinks (26%). These products often consumed by children, so there is a real threat to their health and future of the nation. We encourage parents of small children and pupils to—exclude sweet water from their diet and when buying confectionery to pay attention to their composition and not to buy products with synthetic food dyes.
Keywords: кафедра технології оздоровчих продуктів; синтетичні харчові барвники; колір; харчові продукти; натуральні харчові барвники; synthetic food dyes; color; food products; natural food coloring